(untitled) (Research, Society and Development, 2021)
Objective: To evaluate if there are differences for yield, chemical composition and, consequently, antimicrobial activity of the essential oils of Plectranthus amboinicus when submitted to crops with different fertilizations in the same period of the year. Methodology: Plectranthus amboinicus was grown with two different types of fertilization for 75 days. The extraction of essential oil from the leaves was through hydrodistillation with Clevenger and the identification of its chemical constituents was performed by gas chromatography coupled with mass spectrometry. The antimicrobial activity was determined by the broth microdilution technique. Results: Variations in yield, chemical composition and antimicrobial activity of essential oil were found in samples grown using different organic fertilizers at the same time. The best results were obtained in the sample of essential oil fertilized with bovine manure, yielding 1.65% and Carvacrol (58.6%), γ-Terpinene: (15.1%) and p-Cymene: (8.2%) as majorities. Conclusion: The majorities Carvacrol, γ-Terpinene and p-Cymene were more abundant in the cultivation with organic fertilization of bovine manure type. Likewise, the best antimicrobial potential detected by the essential oil against E. coli and C. albicans was due to the cultivation of plants with organic fertilization of bovine manure type. The data suggest that this type of fertilization is adequate to produce the essential oil with better antimicrobial activity and higher quality. Therefore, it is possible to improve the yield, the concentration of the constituents and their antimicrobial response through an affordable organic fertilizer.